2017
DOI: 10.21037/tau.2017.07.32
|View full text |Cite
|
Sign up to set email alerts
|

The penoscrotal surgical approach for inflatable penile prosthesis placement

Abstract: Optimizing outcomes with placement of inflatable penile prostheses (IPPs) can be challenging, especially in inexperienced hands. In this article, we outline Dr. Köhler’s penoscrotal penile prosthesis surgical approach. We also highlight patient selection, post-operative care and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…In patients undergoing an IPP, a postoperative infection rate of 1%–3% has been previously reported. [ 2 4 5 ] Our post operative infection rate (2.5%) compares favourably. Also, the blind placement of the reservoir into the space of Retzius may be complicated by postoperative inguinal hernia,.…”
Section: Discussionmentioning
confidence: 73%
“…In patients undergoing an IPP, a postoperative infection rate of 1%–3% has been previously reported. [ 2 4 5 ] Our post operative infection rate (2.5%) compares favourably. Also, the blind placement of the reservoir into the space of Retzius may be complicated by postoperative inguinal hernia,.…”
Section: Discussionmentioning
confidence: 73%
“…Historically, a variety of compressive tape dressings have been described by IPP implanters in an effort to provide wound coverage and facilitate hemostasis. 8 Many of these have been either too cumbersome or potentially harmful, leading in some instances to penile necrosis, as with the Coban-based “Soft Cast.” 7 …”
Section: Discussionmentioning
confidence: 99%
“…Given the patient's young age, extra caution was taken to reduce the risk of infection and device herniation or injury. Evidence has shown that multilayer dartos closure may be associated with improved patient satisfaction and may help prevent future complications 7, 8. Furthermore, the use of Metzenbaum scissors to aid in distal corporal dilation has been reported to be a suitable technique 9 .…”
Section: Discussionmentioning
confidence: 99%